The burning process and temperature profile of double fires in a tunnel: An experimental study. (July 2022) - Zhao, Jinlong; Cui, Xinyuan; Yao, Yongzheng; Yang, Rui; Chen, Changkun
Highlights: The burning rate and process for double fires was studied in a model-scale tunnel. Longitudinal ceiling temperature profile showed significant influence for the temperature between double fires. A longitudinal ceiling temperature attenuation model was developed for double fires. A maximum ceiling temperature rise model was revised by introduced S/D. Abstract: In the event of double fires in tunnels, the combustion is strengthened and the smoke movement is restricted by the strong flame plumes. Heavy smoke accumulates rapidly between the two fires, which can result in serious casualties. For this paper, a series of experiments was carried out using a 1:10 scale tunnel, to primarily investigate the fire evolution and ceiling temperature distribution as a function of burner size and spacing. The burning process, the longitudinal ceiling temperature profile and the maximum temperature rise were measured and analyzed. The results show that the time from ignition to when the fire reaches a stable stage is obviously shorter than for a single fire. Furthermore, the steady burning rate is greater than that for a single fire with the same burner size. This higher steady-burning rate decreases as burner spacing increases, but increases with increasing burner size. This is due to the change in radiative heat feedback from the flame to the fuel surface. The longitudinal ceiling temperature profile shows a "double-hump", with the hump values being dependent on the burner spacing. The ceiling temperature between the two fires in a double fire is obviously increased compared to that of a single fire, which can be attributed to the accumulation of smoke and heat between the two flames. The longitudinal ceiling temperature away from the double fires shows an exponentially attenuated trend and the corresponding model is revised. Finally, a maximum temperature rise model is established by introducing burner spacing. This model was validated with the experimental data. These new findings can be used for risk assessment of double fire accidents and to determine the best strategies for personnel evacuation from a tunnel.